1981
DOI: 10.1021/ar00065a003
|View full text |Cite
|
Sign up to set email alerts
|

Gas-phase reactions of organic anions as studied by the flowing afterglow technique

Abstract: It is as futile to try and understand reactions in solution by studying them in the gas phase as to try to reach Paradise by way of Kensal Green.W. John Albery2 When ionic reactions occur in solution the solvent molecules play an important, often dominant, role. In order to investigate the reactions themselves, unobscured by the effects of solvation, an increasing number of studies of gas-phase reactions between ions and molecules are being carried out. The study of organic cations in the gas phase has a long … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0

Year Published

1983
1983
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(50 citation statements)
references
References 33 publications
0
50
0
Order By: Relevance
“…4 We were able to show that the rates of reaction of the two halides differed profoundly in the way they responded to nucleophiles, and concluded that silanes did, indeed, react by way of a pentacovalent intermediate.…”
Section: B Summary Of the Most Important Resultsmentioning
confidence: 89%
“…4 We were able to show that the rates of reaction of the two halides differed profoundly in the way they responded to nucleophiles, and concluded that silanes did, indeed, react by way of a pentacovalent intermediate.…”
Section: B Summary Of the Most Important Resultsmentioning
confidence: 89%
“…Reactions of the selected ion can then be monitored without complication from reactions of other ions. In an experiment analogous to a flowing afterglow selected-ion flow tube (SIFT) experiment (42), Kleingeld and Nibbering (43) studied the gas-phase reaction of protonated methanol ions with neutral methanol molecules using naturally occurring lsO isotope labeling. Two mechanisms have been proposed for the formation of protonated dimethyl ether ion:…”
Section: B Natural-abundance "Labeling"mentioning
confidence: 99%
“…In contrast, gas phase reactions can exhibit potential energy wells corresponding to entrance and exit channel complexes, in particular for reactions involving ions (see, e.g., Refs. [1][2][3]. Experiments on massselected clusters in vacuo are therefore well-suited for studying the fundamental physics of chemical reactions, starting from entrance channel complexes.…”
Section: Introductionmentioning
confidence: 99%
“…This dissociative swave capture reaction 21 is strongly exothermic and the energies involved have been well-characterized. 21,22 Depending on the time scale of electron transfer vs. intramolecular vibrational relaxation to a "bath" of solvent, solvation of the complex ion with Ar atoms can be used to quench electron transfer (see Figure 1), resulting instead in evaporation of the weakly bound Ar atoms from the complex CH 3 This feature of Ar solvation can be used to gain some information on the barrier height for electron transfer. 18,23,24 In the present work, we demonstrate vibrationally mediated electron transfer from a nitromethane anion to a methyl iodide molecule in a bimolecular complex.…”
Section: Introductionmentioning
confidence: 99%